EFFECT OF PUMPKIN OIL AND VITAMIN E ON LEAD INDUCED TESTICULAR TOXICITY IN MALE RATS - Soheir Ahmed Al-Masri (Journal of Animal and Plant Sciences, 2015)
Lead poisoning has been recognized as a major public health risk particularly in developing countries. So the principal aim of this study was occurred to evaluate the protective effect of pumpkin oil and vitamin E on lead induced testicular toxicity in male rats. Forty Sprague Dawley strain rats weighting 165±5g were divided into five groups (8 rats each).  Groups 1 and 2 acted as negative -ve and positive control +ve, while groups 3, 4 and 5 were administered pumpkin oil, vitamin-E and pumpkin oil plus vitamin E respectively, throughout the study period of the experiment (45 days). After 21 days of the beginning of the experiment, the negative control group -ve was injected with normal saline (1cc) intraperitoneally daily, but control +ve, pumpkin oil and vitamin E groups received lead chloride at a dose 12 mg/kg intraperitoneally daily for twenty four days. Results revealed that lead evoked prominent testicular toxicity, deterioration of sperm characters, and disruption of serum gonad/ pituitary hormone levels luteinizing hormone (LH), follicle stimulating hormone (FSH) and (testosterone). Further, lead markedly raised testicular oxidative-stress (lipid-peroxides), while reduced activity of the antioxidant-enzymes, superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase. These changes were also accompanied by a significant body weight gain along with a rise in food efficiency ratio (FER). Treatment with either or both of vitamin-E and pumpkin-seed oil appreciably ameliorated the Pb-induced anomalies as showed a significantly increased in body weight gain, weigh gain% and FER. Also it showed significant improvement of sperm characters, a significant increase in serum LH, FSH and testosterone hormones and increase in antioxidant enzymes. Combined treatment with both showed a superior testicular protection than their individual responses. These results were agreement with that demonstrated by (Kutlubay et al., 2006 and Jamilah 2013) who reported that the improvement of reproductive efficiency of male rats by vitamin E is attributed to its powerful antioxidant property. It is concluded that pumpkin oil plus vitamin-E administration could reduce the testicular toxicity of lead in male rats. The adverse effects due to its antioxidant properties
Keywords: Lead; vitamin-E; pumpkin oil; testicular toxicity; rats